Comparative Compliance: Digital Piracy, Deterrence, Social Norms, and Duty in China and the United States. (3rd January 2017) - van Rooij, Benjamin; Fine, Adam; Zhang, Yanyan; Wu, Yunmei
Abstract : The study of compliance has been predominantly Western, and we do not know whether existing theories and findings also apply elsewhere. As a first venture in developing a comparative view on compliance, this study seeks to gain a comparative understanding of compliance decision making among Chinese and American students. It studies their decisions in response to two scenarios that offer an opportunity to use pirated online content. It tests how their decisions are shaped by subjective deterrence, social norms, and perceived duty to obey the law, comparing a control group with a group who received an explicit deterrence message from a strong campaign targeting the use of pirated digital content. The results indicate that, regardless of the explicit enforcement context, Chinese students' inclination to engage in digital piracy hinges chiefly on the perceived behavior and approval of others. This stands in contrast to US students. Within an explicit enforcement context, both social norms and perceived enforcement affect US students' decision making, whereas when there is no explicit enforcement context, both social norms and perceived duty to obey the law affect decision making. This study thus provides a warning that compliance theories and findings may not generalize well beyond the Western context. This necessitates the development of comparative compliance studies and more cross‐national replication.